Correlation of Threading Dislocations with the Electron Concentration and Mobility in InN Heteroepitaxial Layers Grown by MBE. (1st January 2020) - Adikimenakis, A.; Chatzopoulou, P.; Dimitrakopulos, G. P.; Kehagias, Th.; Tsagaraki, K.; Androulidaki, M.; Doundoulakis, G.; Kuzmik, J.; Georgakilas, A.
Abstract : The quantitative interdependencies of growth conditions, crystal defects and electrical/electronic properties of InN thin films, grown by plasma-assisted molecular beam epitaxy on GaN (0001) buffer layers have been investigated. InN epilayers with thickness near 700 nm, grown under different substrate temperature and/or growth rate, have been analyzed. Bulk electron concentration (Nbulk ) and mobility values were extracted for each InN film using the inverted version of the multilayer Petritz model, subtracting the conductivity of a corresponding 120 nm InN film. The results indicate a significant reduction of the threading dislocation density by enhancing the diffusion length of indium adatoms during InN growth, through increase of substrate temperature and reduction of growth rate. The electrical characteristics deteriorate with increasing threading dislocation density. Assuming threading dislocations as exclusive sources of donors in InN, their charge state could be between +1 and +2 per c lattice constant length of dislocation line for Nbulk ≈ 4.0–5.7×10 17 cm −3, and approximately +2 or larger for Nbulk ≈ 1.5–1.8×10 18 cm −3 . The scattering effect of threading dislocations is significantly weaker compared to reported theoretical calculations, i.e. it would correspond to an order of magnitude lower threading dislocation density than the experimentally observed density in the range of 10 10 cm −2 .